2023
DOI: 10.1097/ms9.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Activated phosphoinositide 3-kinase delta syndrome 2 associated with Kikuchi–Fujimoto disease: a rare Palestinian case report

Abstract: Introduction: Histiocytic necrotic lymphadenitis (HNL), also known as Kikuchi–Fujimoto disease (KFD), is a rare local lymphadenopathy with a benign course and clinical manifestations such as fever, lymphadenopathy, rash, hepatosplenomegaly, central nervous system (CNS) symptoms, and hemophilic cell syndrome. It was first identified by Japanese pathologists Kikuchi and Fujimoto. KFD damages the meninges, the brain parenchyma, and peripheral nerves in addition to the CNS. Neurological symptoms may ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hemophagocytic lymphohistiocytosis (HLH)-like clinical pictures have been described, in one case followed by Hodgkin’s lymphoma. One case study reported an association of APDS2 with Kikuchi-Fujimoto syndrome ( 36 ), another presented with gut-associated T-cell lymphoproliferative disease ( 37 , 38 ). Thus, careful histological examination of lymph nodes by an experienced pathologist is required to avoid unnecessary administration of cytostatic drugs ( 34 , 35 ).…”
Section: Symptoms and Long-term Consequencesmentioning
confidence: 99%
“…Hemophagocytic lymphohistiocytosis (HLH)-like clinical pictures have been described, in one case followed by Hodgkin’s lymphoma. One case study reported an association of APDS2 with Kikuchi-Fujimoto syndrome ( 36 ), another presented with gut-associated T-cell lymphoproliferative disease ( 37 , 38 ). Thus, careful histological examination of lymph nodes by an experienced pathologist is required to avoid unnecessary administration of cytostatic drugs ( 34 , 35 ).…”
Section: Symptoms and Long-term Consequencesmentioning
confidence: 99%